Post-Revolutionary State Building Processes Democratization or Divergent Paths? - Rashed, Ingi (AUC Knowledge Fountain, 2020)
As many scholars argue that revolutionary changes generally leads to autocratization, evidence from recent revolutionary changes in post USSR republics and Eastern Europe demonstrate that divergent regime types emerge thereafter. On the one hand, the case of Poland in the aftermath of the collapse of USSR demonstrates that the first few years after regime removal from power are crucial to the emerging new regime. Additionally, Poland proved that democratization can emerge if various institutional settings take place hand in hand with the existence of certain dynamics that shape decision making processes and society agency.On the other hand, the case of Serbia after the bulldozer revolution proves that toppling dictatorship does not automatically lead to transition toward democracy. With “only” the replacement of leadership without real and efficient institutional and structural reform plans, and the absence of rule of law that inculcates and protects civil and political rights, a reverse back toward authoritarianism or the emergence of an unstable hybrid regime is the definite outcome. My thesis is concerned with understanding the reasons behind such divergent outcomes of regimes in the aftermath of revolutionary change. Moreover, my thesis adopts a comparative historical analysis design following the lead of Theda Scokpol to compare and map the trajectory of practices while analyzing the cases of Poland and Serbia that had different state building dynamics and different outcomes of regimes. The former is classified by the Freedom House Index as a “Free” State with 84/100 points and the latter is classified as “Partly free” with 66/100 points. Accordingly, I am looking at the context of Poland after the collapse of USSR and the breakdown of its communist regime post 1989-1990 focusing on the different structural and institutional processes that paved the way for the institutionalization of democracy. Then, I analyze the case of Serbia after the Bulldozer revolution in October 2000 to compare the applied reforms that led this regime to be a hybrid one.